Reseña de Fernández Pérez, M. (1999), Introducción a la Lingüística, Barcelona, Ariel. - Penadés Martínez, Inmaculada (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–> Se trata de reseña de Fernández Pérez, M. (1999), Introducción a la Lingüística, Barcelona, Ariel.